2017
DOI: 10.7150/thno.18879
|View full text |Cite
|
Sign up to set email alerts
|

PSMA-Targeted Theranostic Nanocarrier for Prostate Cancer

Abstract: Herein, we report the use of a theranostic nanocarrier (Folate-HBPE(CT20p)) to deliver a therapeutic peptide to prostate cancer tumors that express PSMA (folate hydrolase 1). The therapeutic peptide (CT20p) targets and inhibits the chaperonin-containing TCP-1 (CCT) protein-folding complex, is selectively cytotoxic to cancer cells, and is non-toxic to normal tissue. With the delivery of CT20p to prostate cancer cells via PSMA, a dual level of cancer specificity is achieved: (1) selective targeting to PSMA-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 77 publications
4
56
0
4
Order By: Relevance
“…another class of protein-folding complexes, called chaperonins, gained interest with the recognition that cancer cells highly express these mediators of protein-folding [14][15][16][17][18][19][20][21][22][23] . The cytosolic, eukaryotic chaperonin-containing TCP-1 (CCT) is an emerging player in neoplastic transformation with potential for development as a novel diagnostic marker and therapeutic target.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…another class of protein-folding complexes, called chaperonins, gained interest with the recognition that cancer cells highly express these mediators of protein-folding [14][15][16][17][18][19][20][21][22][23] . The cytosolic, eukaryotic chaperonin-containing TCP-1 (CCT) is an emerging player in neoplastic transformation with potential for development as a novel diagnostic marker and therapeutic target.…”
mentioning
confidence: 99%
“…Genomic amplification of CCT or upregulation of gene expression suggests that CCT could be a marker for oncogenesis 34 . Previous studies reported that the expression levels of different CCT subunits are upregulated in various cancers, such as CCT8 and CCT3 in hepatocellular carcinoma 18,22 or glioblastoma 35 , and CCT2 in prostate, breast, and lung cancers 14,15,21 . Our lab discovered a CCT inhibitor called CT20p that kills cancer cells in a CCT-dependent manner.…”
mentioning
confidence: 99%
“…Subsequent in vivo studies in LNCaP tumor-bearing mice indicated tumor regression of up to 90% with no direct toxicity observed. The most recent inhibitor-toxin conjugate was developed by Flores et al 82 They prepared a HBPE polymer nanoparticle and modified it with folate to target PSMA. To exert a cytotoxic effect on PSMA-positive cancer cells, they encapsulated a peptide called CT20p inside the nanoparticle.…”
Section: Psma Inhibitor-toxin Conjugatesmentioning
confidence: 99%
“…It is an attractive molecular marker for the detection and therapeutic target of primary and metastatic PCa (Maresca et al, 2009). In contrast, targeting of this ligand can be considered as an approach to fight against drug resistance in PCa by improving of the tumor localization and uptake (Flores et al, 2017;Ganju et al, 2014;Kroon, Kooijman, Cho, Storm, & van der Pluijm, 2016).…”
mentioning
confidence: 99%